Bacteriophage-mediated spread of bacterial virulence genes. (February 2015) - Penadés, José R; Chen, John; Quiles-Puchalt, Nuria; Carpena, Nuria; Novick, Richard P
Highlights: Phage-mediated transduction drives bacterial evolution. pac -phages can package any bacterial DNA. Both pac and cos phages can transfer mobile genetic elements. Mobile genetic elements have evolved sophisticated strategies to hijack phage DNA-packaging machinery. Gene transfer agents are phage-like particles involved in horizontal gene transfer. Abstract : Bacteriophages are types of viruses that infect bacteria. They are the most abundant and diverse entities in the biosphere, and influence the evolution of most bacterial species by promoting gene transfer, sometimes in unexpected ways. Although pac -type phages can randomly package and transfer bacterial DNA by a process called generalized transduction, some mobile genetic elements have developed elegant and sophisticated strategies to hijack the phage DNA-packaging machinery for their own transfer. Moreover, phage-like particles (gene transfer agents) have also evolved, that can package random pieces of the producing cell's genome. The purpose of this review is to give an overview of some of the various ways by which phages and phage-like particles can transfer bacterial genes, driving bacterial evolution and promoting the emergence of novel pathogens.